Vaccines: a health insurance of the 21st century - Rappuoli, Rino (Henry Stewart Talks, 2011)
Major health challenges of the 21st Century, Causes of increased life expectancy: conquest of infectious diseases, Life expectancy is growing beyond prediction, New technologies in the last 30 years, Safety of vaccines, Meningococcal disease, Vaccines for Meningococcus C, Meningococcus B, Reverse vaccinology allows us to target many pathogens that were difficult or impossible before, Prevention of cancers, Vaccination and our aging society, H5N1 vaccine, Vaccines to address poverty, Novartis Vaccines Institute for Global Health